My Brother, My Lover, My Self: Traditional Masculinity in the Hong Kong Action Cinema of John Woo - Koven, Mikel (Ethnologies, 1997)
Hong Kong Chinese filmmaker John Woo has been “misread” and his work “misappropriated” by exoteric factors in the methodology of Western film studies. His films, specifically his gangster genre films, have been labeled by Western film critics as “homoerotic”. This is not a derision of Woo’s crime thrillers, per se, in so far as none of these critics have used “homoeroticism” in a negative fashion, that homoeroticism in film is a bad thing, but Koven does believe that to read Woo’s gangster films as homoerotic misses the cultural producers’ point. Woo’s films certainly deal with male-male relationships, but to see these relationships in terms of erotic desire “misreads” the Hong Kong Chinese understanding of the codes of masculine behaviour. Instead, the author posits an alternative reading, alternative, that is, to the hegemony of the Western cultural studies discourse; John Woo’s action cinema can be approached as experiential phenomena regarding the construction of a kind of traditional masculine behaviour among the Hong Kong Chinese.